(untitled) (LACCEI, 2024)
The main objective of this research was to determine the relationship that exists between indebtedness and the financial culture of the administration students of the Universidad Privada Antenor Orrego de Trujillo Campus in the year 2022. The study was carried out using the non-experimental qualitative approach of correlational descriptive design, also two questionnaires of 14 items each were used as data collection instruments which were validated using the Kuder-Richardson technique with a result of 0.77 these were used to analyze a population of 279 students belonging to the Economically Active Population (EAP) of legal age, belonging to the seventh cycle onwards and who have a credit card and/or loans with financial entities during the period from August to December of the year 2022, from which a sample of 162 students was extracted with a confidence level of 95% and a sampling error of 5%. The results obtained were that 59.88% of the students have a low level of indebtedness and 48.15% demonstrated a medium level of financial literacy. The main conclusion was that a low positive relationship was determined between the indebtedness of Administration students with the dimensions of financial culture considered in this research, such as knowledge, ability and financial attitude.